Virgin Martyrs : Legends of Sainthood in Late Medieval England - Winstead, Karen A. (Karen Anne), 1960- (Book collections on Project MUSE., 1997)
"Stories of the torture and execution of beautiful Christian women first appeared in late antiquity and proliferated during the early Middle Ages, and virgin martyrs were still the most popular female saints in the late medieval period. Their legends, in countless retellings through the centuries, preserved a standard plot - the heroine resists a pagan suitor, endures cruelties inflicted by her rejected lover or outraged family, works miracles, and dies for Christ. That sequence was embellished by incidents emblematic of the specific saint: Juliana's battle with the devil, Barbara's immurement in the tower, Katherine's encounter with spiked wheels." "Karen A. Winstead examines this seemingly static story form and discovers subtle shifts in the representation of the virgin martyrs, as their legends were adapted for changing audiences in late medieval England. The saints' portrayals participated in and were shaped by the cultural debates and contests for authority that marked an era of political instability, rapid social change, and increasing religious dissent."--Jacket